Pengaruh Gaya Kepemimpinan Dan Budaya Organisasi Terhadap Kepuasan Kerja Pegawai Pada Dinas Perdagangan, Perindustrian Dan Koperasi, Usaha Kecil Menengah Kabupaten Buleleng - Gde Agung Satria; I Gede Pebriyana Merta Putra (Sekolah Tinggi Ilmu Ekonomi Satya Dharma, 2022)
The purpose of this study was to determine: (i) the influence of leadership style on job satisfaction and (ii) the influence of organizational culture on employee job satisfaction at the Department of Trade, Industry and Cooperatives, District Small and Medium Enterprises. Data collection techniques used in this study are in the form of questionnaires and documentation. In this study, the entire population was used as the research sample, amounting to 122 people. The data analysis technique used is simple regression analysis using SPSS 20 for windows. The results of this study indicate that: (i) leadership style has a positive and significant effect on job satisfaction at the Department of Trade, Industry and Cooperatives, Small and Medium Enterprises, Buleleng Regency. This is evidenced by the regression equation Y = 2.404 + 0.940 (X1) + 1.360, the correlation coefficient value is 0.901 with a very strong category, and the t-test value is 22.757 which is smaller than t table (22.757>1.985) with a significance of 0.000 (sig<0 ,05). This means that the more appropriate the leadership style, the better the level of employee job satisfaction at the Department of Trade, Industry and Cooperatives, Small and Medium Enterprises, Buleleng Regency. (ii) Organizational culture has a positive and significant effect on Job Satisfaction at the Department of Trade, Industry and Cooperatives, Small and Medium Enterprises, Buleleng Regency. This is evidenced by the regression equation Y = -0.614 + 1.051 (X2) + 1.127, the correlation coefficient value is 0.940 with a very strong category, and the t-test value is 30.125 which is smaller than ttable (30.125>1.985) with a significance of 0.000 (sig< 0.05). This means that the better the Organizational Culture, the better the level of employee job satisfaction at the Department of Trade, Industry and Cooperatives, Small and Medium Enterprises, Buleleng Regency”.